Studies on InP-based heterojunction bipolar transistors (HBTs) for MMIC applications - Wang, Hong (2008)
The main objectives of this thesis are to develop the fabrication technology for InP/InGaAs Heterojunction Bipolar Transistors (HBTs) and conduct comprehensive studies on the dc and microwave characteristics of the HBTs. The developed HBT technology is also intended to demonstrate its suitability for Monolithic Microwave Integrated Circuit applications.